Imaging characteristics of pediatric primary thymic lymphoepithelioma-like carcinoma: case reports of four children with a literature review - Zhu, Xiao-dong; Fang, Yuan; Wang, Xiao-yu; Hu, Jun; Gu, Dong-hao; Yao, Qiong; Qiao, Zhong-wei (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to analyze the imaging characteristics of lymphoepithelioma-like carcinoma (LELC) in children's thymi.MethodsFour pediatric cases of primary thymic LELC confirmed by needle biopsy pathology from our research center were enrolled. All children underwent an enhanced chest computed tomography (CT) examination. In addition, 11 cases of pediatric thymic LELC with CT manifestations reported in the literature over the past 20 years were combined to explore their imaging characteristics.ResultsIn our research center, there were four cases, all boys, with an average age of 11.25 ± 2.87 years. CT showed a soft tissue mass in the anterior mediastinum in all four cases, with the mass being lobulated or roughly circular and growing laterally. The largest mass had a diameter of 120 mm, with an average of 90 ± 21.6 mm. In three cases, the mass showed cystic necrosis, which enhanced unevenly, and in three cases, small blood vessels were seen traversing the mass. Two cases had an invasion of the pleura and lung with associated pleural effusion. In two cases, vascular reconstruction showed blood supply from branches of the internal thoracic artery, with one case having spinal metastasis. Combined with literature reports of 11 pediatric cases with thymic LELC, a total of 15 cases of thymic LELC were identified: 13 cases were boys, 2 cases were girls, and the average age was 11.2 ± 2.9 years. The largest lesion had a diameter of 160 mm, with an average of 107 ± 27.78 mm. Seven cases had cystic necrosis, 4 cases had calcification, 5 cases did not mention the enhancement method, and the remaining 10 cases showed uneven enhancement. Furthermore, six cases had tumor invasion of adjacent large blood vessels; six cases had pleural effusion; five cases had pleural invasion; six cases had metastasis to the mediastinal, hilar, or axillary lymph nodes cases had pulmonary metastasis; and four cases had bone metastasis.ConclusionThymic LELC in children showed a higher incidence in boys. The imaging characteristics of pediatric thymic LELC manifested as a large mass located in the anterior mediastinum, with highly malignant features and metastasis.